Mettre en jeu le voyage dans le temps : de la réappropriation vidéoludique d’un sous-genre de la science-fiction - Clément Personnic; Yannick Kernec’h (ReS Futurae)
The time travel genre might be considered as one the major science fiction themes, maybe a sub-genre in itself on account of the invariable characteristics of its variations in litterature, cinema - starting in the fifties- and more recently in television seriality and video games. This study aims to emphasise on the ways and means for time travel reappropriation by video games. Many video games genres give themselves over to time manipulation like platforms games, shooting games or even role playing games. Thus what can be assimilated in a ludic sense from such a sub-genre ? What become of those elements once incorporated ? Finally how to reconcile in such a videoludic continuum the freedom related to the (relative) time flow mastery on one hand and more general interactive possibilities (also relatives) on the other hand ? Furthermore other necessities related to an always significant narrative are also to be taken in to consideration. If time traveling in games can be subjected to little dramatization for pure gaming contextualization, this also allows some originals game design through direct time manipulation implementation to the ludic system. We call such a reappropriation generic assonance.